2013
DOI: 10.1021/ja312367k
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition and Kinetic Resolution of Aromatic Amines via Supramolecular Chiral Nanocapsules in Nonpolar Solvents

Abstract: Herein we report the first example of chiral recognition and kinetic resolution of aromatic amine guests using supramolecular nanocapsules assembled from cyclodextrin derivatives in nonpolar media. With these nanocapsules, an extremely high chiral recognition of 1-(1-naphthyl)ethylamine (1) in cyclohexane was achieved, with a binding selectivity of up to 41 for (S)-1 over (R)-1. In addition, kinetic resolution of 1 through enantioselective N-acylation was accomplished with an enantiomeric excess of up to 91%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 30 publications
2
43
1
1
Order By: Relevance
“…The X-ray crystalline structure showed that the 4i molecule was included within the cavity of the TIPS-β-CD dimer in a similar fashion to a TIPS-β-CD-(S)-1-(1-naphthyl)ethylamine 6 or TIPS-β-CD-pyrene 10 complex previously reported (Figure 3). Interestingly, both the carbonyl oxygen and chlorine atoms of the 1-naphthoyl chloride molecule formed hydrogen bonds with the 3-OH group of the upper and lower TIPS-β-CDs, respectively (the O···O and Cl···O distances are 2.68 and 3.14 Å, respectively).…”
Section: The Formation Of Inclusion Complexes Between Tips--cds and supporting
confidence: 60%
See 3 more Smart Citations
“…The X-ray crystalline structure showed that the 4i molecule was included within the cavity of the TIPS-β-CD dimer in a similar fashion to a TIPS-β-CD-(S)-1-(1-naphthyl)ethylamine 6 or TIPS-β-CD-pyrene 10 complex previously reported (Figure 3). Interestingly, both the carbonyl oxygen and chlorine atoms of the 1-naphthoyl chloride molecule formed hydrogen bonds with the 3-OH group of the upper and lower TIPS-β-CDs, respectively (the O···O and Cl···O distances are 2.68 and 3.14 Å, respectively).…”
Section: The Formation Of Inclusion Complexes Between Tips--cds and supporting
confidence: 60%
“…Similar to our recent study using acid anhydride as an acylation reagent, 6 cyclohexane was chosen as the solvent, in which the supramolecular TIPS--CD nanocapsule showed high chiral recognition towards 1 (Table 1, entry 1). A mixture of primary amines 1-3, TIPS--CD (5.0 equiv), and triethylamine (1.0 equiv) in cyclohexane was stirred for 1 h to reach complexation equilibrium.…”
Section: Enantioselective N-acylation Of Primary Amines In the Presenmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclodextrins, cyclic oligomers of D-glucopyranose units with a conical chiral cavity, have chirality sensing ability through host-guest interactions [40][41][42] . Consequently, cyclodextrins are employed in various matrixes for applicable enantiomeric selectivity and separation, e.g., microspheres, nanochannels, electrodes, and the stationary phase of columns [43][44][45][46] .…”
mentioning
confidence: 99%